2021
DOI: 10.1098/rsos.210511
|View full text |Cite
|
Sign up to set email alerts
|

Non-topographic current contrast in scanning field emission microscopy

Abstract: In scanning field emission microscopy (SFEM), a tip (the source) is approached to few (or a few tens of) nanometres distance from a surface (the collector) and biased to field-emit electrons. In a previous study (Zanin et al. 2016 Proc. R. Soc. A 472 , 20160475. ( doi:10.1098/rspa.2016.0475 )), the field-emitted current was found to change by approximately 1% at a monatomic surface step (approx. 200 pm thick). Here we prepare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The above process could be expected to hold for all carbon-covered tungsten surfaces since they are the result of purely coulombic interactions. We tentatively argue that they may also be responsible for the observed decrease in the workfunction of the carboncovered tungsten collector (110) surface in [1].…”
Section: Results-discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The above process could be expected to hold for all carbon-covered tungsten surfaces since they are the result of purely coulombic interactions. We tentatively argue that they may also be responsible for the observed decrease in the workfunction of the carboncovered tungsten collector (110) surface in [1].…”
Section: Results-discussionmentioning
confidence: 78%
“…Several experiments at ETH [1] under the title Scanning Field Emission Microscopy have demonstrated that tungsten (110) surfaces covered by monolayers of several adatoms in various complicated structures (such as 12 × 15) acting as collectors under an external electric field show increased received current compared to the pure metallic tungsten substrate. The experiments referred to field emission in a nanometric tunnel diode operating in a point facing plane configuration in which the current was shown to increase by an epitaxial carbon or other adatom cover of the tungsten collector.…”
Section: Introductionmentioning
confidence: 99%